Dry eye syndrome: comprehensive etiologies and recent clinical trials - Huang, Ruojing; Su, Caiying; Fang, Lvjie; Lu, Jiaqi; Chen, Jiansu; Ding, Yong (International ophthalmology, 2022)
Dry eye syndrome (DES) is multifactorial and likely to be a cause of concern more so than ever given the rapid pace of modernization, which is directly associated with many of the extrinsic causative factors. Additionally, recent studies have also postulated novel etiologies that may provide the basis for alternative treatment methods clinically. Such insights are especially important given that current approaches to tackle DES remains suboptimal. This review will primarily cover a comprehensive list of causes that lead to DES, summarize all the upcoming and ongoing clinical trials that focuses on treating this disease as well as discuss future potential treatments that can improve inclusivity.